2021
DOI: 10.1186/s12864-021-07755-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genomic regions for chicken egg number traits based on genome-wide association study

Abstract: Background Since the domestication of chicken, various breeds have been developed for food production, entertainment, and so on. Compared to indigenous chicken breeds which generally do not show elite production performance, commercial breeds or lines are selected intensely for meat or egg production. In the present study, in order to understand the molecular mechanisms underlying the dramatic differences of egg number between commercial egg-type chickens and indigenous chickens, we performed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
0
10
1
Order By: Relevance
“…org/ cgi-bin/ QTLdb/ GG/ index). The regions identified in our study were 1.9 Mb apart from those reported by Zhao et al, which were carried out in more than a dozen breeds, including White Leghorn and Rhode Island Red chickens [23]. Although the results were different between the present study and that of Zhao et al, they suggest that GGA Z is an important genetic region involved in egg production.…”
Section: Discussioncontrasting
confidence: 93%
“…org/ cgi-bin/ QTLdb/ GG/ index). The regions identified in our study were 1.9 Mb apart from those reported by Zhao et al, which were carried out in more than a dozen breeds, including White Leghorn and Rhode Island Red chickens [23]. Although the results were different between the present study and that of Zhao et al, they suggest that GGA Z is an important genetic region involved in egg production.…”
Section: Discussioncontrasting
confidence: 93%
“…Based on these results, a number of genes associated with puberty were identified. The GAMT gene plays an important role in embryonic development and the reproductive system ( Braissant et al, 2005 ; Zhao et al, 2021 ). SOHLH1 is a multifunctional regulator of the network required for oocyte maintenance and differentiation during early folliculogenesis ( Wang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ling et al (2014) identified 12 genes associated with high fecundity in Anhui white goats. Based on metabolomics, Zhou et al (2021) identified polymorphisms in IRS1 were associated with growth efficiency traits in Chinese black Tibetan sheep and Zhang et al found stallfeeding modified the content of protein and fat, tenderness, water holding capacity, and texture of the longissimus lumborum of Tibetan sheep (Zhang et al, 2021). Based on 16S rRNA gene pyrosequencing, Gui et al (2021) found that supplementation of concentrate in the cold season improved the rumen microbial abundance of Tibetan sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Since, brown adipose tissue acts as a thermal regulator and heat generator for the body upon cold exposure 28 , 29 , the positive selection of gene involved in the development of this tissue can be vital for Bactrian camels that have adapted to cold climates. The CAMK4 gene is known as a domestication-related gene in sheep 30 and has been shown to play an important role in the reproduction of mice 31 , sheep 32 , and chicken 33 , 34 . This gene is also associated with the formation of long-term memory 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%